Studer, Helen (audio interview #2 of 4) - Studer, Helen (b. 5/27/1898 - d. 8/00/1981 ); Cleary, Cindy, interviewer
INTERVIEW DESCRIPTION - Studer remained nervous in this second interview, and continued to leaf through photographs and asked repeatedly that the recorder be turned off. Despite this, she was open and direct and spoke wt. little prompting. 6/11/1980